Influence of substrate dimensionality on the growth mode of epitaxial 3D-bonded GeTe thin films: From 3D to 2D growth. (15th April 2019) - Hilmi, Isom; Lotnyk, Andriy; Gerlach, Jürgen W.; Schumacher, Philipp; Rauschenbach, Bernd
Abstract: The pseudo-binary line of Sb2 Te3 -GeTe contains alloys featuring different crystalline characteristics from two-dimensionally (2D-) bonded Sb2 Te3 to three-dimensionally (3D-) bonded GeTe. Here, the growth scenario of 3D-bonded GeTe is investigated by depositing epitaxial GeTe thin films on Si(111) and Sb2 Te3 -buffered Si(111) substrates using pulsed laser deposition (PLD). GeTe thin films were grown in trigonal structure within a temperature window for epitaxial growth of 210–270 °C on unbuffered Si(111) substrates. An unconventional growth onset was characterized by the formation of a thin amorphous GeTe layer. Nonetheless, the as-grown film is found to be crystalline. Furthermore, by employing a 2D-bonded Sb2 Te3 thin film as a seeding layer on Si(111), a 2D growth of GeTe is harnessed. The epitaxial window can substantially be extended especially towards lower temperatures down to 145 °C. Additionally, the surface quality is significantly improved. The inspection of the local structure of the epitaxial films reveals the presence of a superposition of twinned domains, which is assumed to be an intrinsic feature of such thin films. This work might open a way for an improvement of an epitaxy of a 3D-bonded material on a highly-mismatched substrate (e.g. Si (111)) by employing a 2D-bonded seeding layer (e.g. Sb2 Te3 ). Graphical abstract: Unlabelled Image Highlights: Epitaxial 3D-bonded GeTe thin films are grown by pulsed laser deposition on 3D- and 2D-bonded substrates Deposition on 2D-bonded substrates allows the epitaxial growth at low substrate temperatures A possibility of improving surface quality of epitaxial 3D-bonded thin films by employing a 2D-bonded seeding layer is shown Formation of overlapped twin domains with characteristic lamellar structure in HRTEM